Species, the value of - Rolston, Holmes, 1932-2025, author; Wiley-Blackwell, publisher (Colorado State University. Libraries, 2013)
Humans value wild species finding instrumental uses for them and products derived from them. Wild species have important roles in ecosystems and must be conserved in habitats in which they are adapted fits. Species are also good in themselves, good in their own right. Often there is a "win-win" result from biodiversity, benefits simultaneously for humans and for flourishing species. But often there are tradeoffs, bringing moral assessments of appropriate concern for species. The speciation process and its species products have persisted several billion years. Humans now jeopardize this valuable evolutionary history, and ought not to shut down the life stream, the most destructive event possible.
Keywords: species; instrumental value; intrinsic value; biodiversity; biosphere; ecosystems; respect for life; speciation; extinction; evolution